Evaluation of the catalytic specificity, biochemical properties, and milk clotting abilities of an aspartic peptidase from Rhizomucor miehei - Silva, Ronivaldo Rodrigues da [UNESP]; Souto, Tatiane Beltramini; Oliveira, Tassio Brito de [UNESP]; Goncalves de Oliveira, Lilian Caroline; Karcher, Daniel; Juliano, Maria Aparecida; Juliano, Luiz; Oliveira, Arthur H. C. de; Rodrigues, Andre [UNESP]; Rosa, Jose C.; Cabral, Hamilton (Springer, 2016)
In this study, we detail the specificity of an aspartic peptidase from Rhizomucor miehei and evaluate the effects of this peptidase on clotting milk using the peptide sequence of k-casein (Abz-LSFMAIQ-EDDnp) and milk powder. Molecular mass of the peptidase was estimated at 37 kDa, and optimum activity was achieved at pH 5.5 and 55 A degrees C. The peptidase was stable at pH values ranging from 3 to 5 and temperatures of up 45 A degrees C for 60 min. Dramatic reductions in proteolytic activity were observed with exposure to sodium dodecyl sulfate, and aluminum and copper (II) chloride. Peptidase was inhibited by pepstatin A, and mass spectrometry analysis identified four peptide fragments (TWSISYGDGSSASGILAK, ASNGGGGEYIFGGYDSTK, GSLTTVPIDNSR, and GWWGITVDRA), similar to rhizopuspepsin. The analysis of catalytic specificity showed that the coagulant activity of the peptidase was higher than the proteolytic activity and that there was a preference for aromatic, basic, and nonpolar amino acids, particularly methionine, with specific cleavage of the peptide bond between phenylalanine and methionine. Thus, this peptidase may function as an important alternative enzyme in milk clotting during the preparation of cheese.
Keywords: Aspartic protease; Biochemical characterization; Intramolecularly quenched fluorogenic substrate; Rhizomucor miehei; Specificity